RANCANG BANGUN SMART AGRICULTURE UNTUK TANAMAN HORTIKULTURA MENGGUNAKAN MIKROKONTROLER - pebri, nemisius; Fadillah, Nurul; Chryostomos Hendro Yuwono, Yohanes; Rusyda , Nanda; Yuwono Tharam , Medi (entries, 2024)
Soil is a primary factor in agriculture that must be carefully considered to achieve optimal results. Irrigation, fertilization, and soil acidity monitoring are crucial for plant growth. Soil moisture influences plant growth, and the type and composition of the soil also play an important role. Automated drip irrigation and soil pH monitoring methods are essential for horticultural plants to grow well and efficiently. An automatic drip irrigation system, scheduled fertilization, and soil pH monitoring aid in plant growth and monitoring efficiency. This device uses capacitive sensors to detect soil moisture and pH levels. If the soil moisture is below 45%, the water pump will activate until the moisture reaches 75%. The detected moisture and pH levels are displayed on an LCD. The Arduino Uno controls the moisture using a soil moisture sensor, displaying wet or dry conditions. The pH sensor displays the soil acidity level ranging from 2 to 14 on the LCD.